Transcutaneous vagus nerve stimulation for Parkinson’s disease: a systematic review and meta-analysis - Jiatong Shan; Jiatong Shan; Jiatong Shan; Zehong Li; Minxiu Ji; Miao Zhang; Caidi Zhang; Yikang Zhu; Zhen Feng (Frontiers in Aging Neuroscience)
BackgroundTranscutaneous vagus nerve stimulation (tVNS) has emerged as a novel noninvasive adjunct therapy for advanced Parkinson’s disease (PD), yet no quantitative analysis had been conducted to assess its therapeutic effect.ObjectivesThis review aimed to investigate the efficacy of tVNS on motor function, other potential clinical targets and its safety in various treatment conditions.MethodsWe searched six databases for randomized controlled trials (RCTs) that involved treating PD patients with tVNS. Primary outcome was motor functions, including severity of motor signs, functional mobility and balance, and gait parameters. Secondary outcomes were cognition, emotion, sleep related impairments, patient reported non-motor outcomes, and any adverse events. All outcomes were classified and analyzed according to the treatment duration and medication condition of an included study. Risk of bias was evaluated by referencing Cochrane risk of bias tool 1.0. Data was analyzed by Revman 5.4.Results6 RCTs with 176 PD patient were included. Several motor functions and non-motor functions measured during on-medication condition (severity of motor signs −0.48 [95% CI −0.93, −0.04], gait −0.48 [95% CI −0.85, −0.1], patients reported non-motor outcomes −0.4 [95% CI −0.78, −0.03]), improved significantly. However, verbal fluency, sleep-related impairment, and fatigue were negatively impacted by tVNS during on-medication condition. No distinct adverse events were reported.ConclusiontVNS is a relatively safe adjunct treatment for PD. It has small to moderate therapeutic effects on motor functions and may negatively impact on a few other outcomes. Quality level of the evidence is low and further research is warranted.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#recordDetails, identifier CRD42024503322 (PROSPERO).